Effect of biomass origins and composition on stability of hydrothermal biocrude oil. (15th October 2021) - Wang, Yingxian; Zhang, Yuanhui; Yoshikawa, Kunio; Li, Hugang; Liu, Zhidan
Graphical abstract: Highlights: Eight aging pathways were proposed for biocrudes from different feedstocks. Only cornstalk biocrude oil became solid phase after 7 days storage. The reason for cornstalk biocrude aging was due to the phenols from carbohydrates. The viscosity changes of biocrude oil were not equivalent to the molecular weight. The nitrogen compounds from proteins were one reason that caused the oil aging. Abstract: High contents of oxygenated and nitrogenous compounds in the biocrude oil produced from hydrothermal liquefaction (HTL) would result in undesirable oil qualities, and deteriorating storage stability. This study investigated the aging behavior and the storage stability of biocrude oils from different biomass with different origins and biochemical components using an accelerated aging method. HTL biocrude oils converted from Spirulina, cornstalk, and swine manure were stored in anoxic and dark environment at 80 °C for 7 days. The biocrude oil obtained from cornstalk became a solid phase after one day due to the oxidation and polymerization of phenols. The changing rate of the viscosity showed that the aging level of the three oils was in the order: cornstalk > swine manure > Spirulina . The changes in the molecular weight and the boiling point indicated the higher changing rate of viscosity of the biocrude oils due to the polymerization of the light fraction. The change rate of HHV of three biocrude oil samples was only 0.88–2.55%, and the water content decreased by 18.5–75.3% during storage. Phenols, nitrogenous compounds, and organic acids in biocrude oil produced from carbohydrates, proteins, and lipids were the main reason for the oil aging.